2015
DOI: 10.1371/journal.pone.0127907
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity without Efficacy of an Adenoviral Tuberculosis Vaccine in a Stringent Mouse Model for Immunotherapy during Treatment

Abstract: To investigate if bacterial persistence during TB drug treatment could be overcome by modulation of host immunity, we adapted a clinically-relevant model developed for the evaluation of new drugs and examined if immunotherapy with two adenoviral vaccines, Ad35-TBS (AERAS-402) and Ad26-TBS, could shorten therapy in mice. Even though immunotherapy resulted in strong splenic IFN-γ responses, no effect on bacterial replication in the lungs was seen. Multiplex assay analysis of lung samples revealed the absence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…1,2 They trigger a potent inflammatory response, 3,4 which initiates adaptive immune responses to the transgene product and the antigens of the Ad vector. 5 This has led to the development of different Ad serotypes as vaccine carriers for a plethora of antigens derived from viruses, 6-10 bacteria, 11,12 parasites, 13,14 or tumor cells, [15][16][17] which have consistently induced potent and sustained B and T cell responses to the transgene products.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 They trigger a potent inflammatory response, 3,4 which initiates adaptive immune responses to the transgene product and the antigens of the Ad vector. 5 This has led to the development of different Ad serotypes as vaccine carriers for a plethora of antigens derived from viruses, 6-10 bacteria, 11,12 parasites, 13,14 or tumor cells, [15][16][17] which have consistently induced potent and sustained B and T cell responses to the transgene products.…”
Section: Introductionmentioning
confidence: 99%
“…One area of interest in the TB vaccine field is whether the mucosal delivery of vaccines to lungs that have existing mycobacterial immunity can increase populations of potentially protective T cell subsets systemically, and, importantly, locally. Several studies in mice have explored the use of post-exposure vaccines either as a stand-alone intervention (24) or as an adjunct to antibiotic therapy (25)(26)(27)(28)(29)(30). Of these, one that tested mucosal vaccine delivery of an adenovirus vectored vaccine resulted in significantly increased antigen-specific lung CD8 T cells and markedly reduced bacterial burden after withdrawal of antibiotic therapy (30).…”
Section: Discussionmentioning
confidence: 99%
“…At present, there are limited reports evaluating the immunogenicity and immune efficacy of vaccines in infected animals. Alyahya et al [ 39 ] reported that the cellular immune response and bacterial loads in tissues were decreased in mice following antibiotic treatment. In conclusion, the vaccine group showed similar changes in cellular immunology and organ bacterial loads to the antibiotic treatment group in the study by Alyahya and colleagues, suggesting that the AEC/BC02 vaccine provided effective anti-TB immune protection against latent Mtb infection in mice.…”
Section: Discussionmentioning
confidence: 99%